Análisis costo-efectividad en el Altiplano Sur de Bolivia: Caso del compost para la quinua - Javier Aliaga Lordemann; Liliana Roca; Norma Feliciano Carvajal (Institute for Advanced Development Studies (INESAD), 2025)
– In the Southern Altiplano of Bolivia, altered climate patterns have negatively impacted the production of essential crops. In particular, quinoa, which has gained global popularity as a superfood, has been affected. The increased demand has placed considerable pressure on local farmers to improve their cultivation practices and adapt to increasingly adverse climatic conditions. The implementation of Good Agricultural Practices (GAP), specifically the use of compost, has emerged as a strategy to enhance soil quality, reduce reliance on harmful chemical fertilizers, and potentially increase crop yields and farmer incomes. This research conducts a cost-effectiveness analysis of compost use in quinoa production in the Southern Altiplano. It is applied by the Institute for Advanced Development Studies (INESAD) within the framework of a pilot project on sustainable production. Compost doses were applied to quinoa plots of small producers, allowing for the evaluation of their impact on crop yields, incomes, and operational costs. The methodology included a cost-benefit analysis of GAP, complemented by a cost-effectiveness analysis. Additionally, carbon footprint measurements were taken before and after implementing composting practices using the Cool Farm Tool, enabling a comprehensive assessment of the economic and environmental benefits associated with compost use. The findings indicate that compost application significantly improves quinoa yields. The average yield increased from 877 kg/ha to 1,109 kg/ha, representing a 26.66% improvement attributable to compost use. Although losses in soil organic matter and nitrogen levels were observed, the compost-treated plots showed a smaller decrease compared to the control plots. The total carbon footprint associated with compost use was higher, as expected, but carbon sequestration in the soil increased by 15%, along with improvements in yield and soil health benefits, justifying this practice economically. The cost analysis revealed that while the initial investment in composting is considerable, the long-term benefits in terms of productivity and sustainability are significant. The study concludes that the adoption of GAP, especially composting, is an effective strategy for improving quinoa production and reducing carbon footprints in the Southern Altiplano. It is essential for farmers to view soil recovery as a long-term investment that could not only enhance immediate productivity but also support agricultural sustainability. Expanding composting implementation on more farms, ensuring producer commitment throughout the study, and promoting the cultivation of native cover crops to improve soil organic matter and carbon sequestration capabilities are recommended. By optimizing agricultural practices and managing costs effectively, farmers can achieve better financial outcomes while contributing to environmental sustainability.
Keywords: Q12; Q13; Q18; Q51; Q54; 330; cost-effectiveness; compost; climate change; compost; carbon footprint; quinoa